DETERMINATIONS OF SOME HEAVY METALS IN VEGETABLES CULTIVATED IN SOME VILLAGES IN DAMBOA, NORTH – EASTERN NIGERIA - Mohammed, Halima Bala; Mohammed, Gwana Adamu; Kolo, Baba Gana; Ahmed, Hamra Abatcha; Kolo, Mu’azu Abdullahi Kofar Na’isa; Aliyu, Abubakar (International Journal of Research -GRANTHAALAYAH, 2019)
With consideration to food hazards and its security, this research study was conducted to determine the concentration levels of some heavy metals in vegetables cultivated in Damboa, Nigeria. Fresh samples of vegetables; Cucumber (cucumis spp) and Onion (Allium cepa) were obtained from the farms in four villages, analysed by using Atomic Absorption Spectrophotometric (AAS) techniques. Results obtained showed variations in concentration in microgram per litre (µg / L). Eight heavy metals were determined; cadmium (Cd), chromium (Cr), copper (Cu), iron (Fe), manganese (Mn), nickel (Ni), lead (Pb) and zinc (Zn). The analysis revealed that; Gumsuri – Ritawa village; the concentration levels in cucumber ranged from - 0.7 ± 0.06 to 5.7 ± 0.06, while in onion ranged from 0.2 ± 0.06 to 4.8 ± 0.06; highest is Cd (5.7 µg / L) in cucumber. Gumsuri – Tolori village, concentration in cucumber ranged from -6.6 ± 0.06 to 0.82 ± 0.02, in onion is 0.27 ± 0.01; highest is Pb (0.9 µg / L) found in onion. Katchalla - Bulari village; it ranged from -1.30 ± 0.06 to 2.71 ± 0.01 in cucumber, and onion is -0.90 ± 0.1 to 3.0 ± 0.1; highest is Ni (3 µg / L) in onion, and the lowest is Pb (- 1.3 µg / L) in cucumber. Nziddamari Village; in cucumber it ranged from -1.0 ± 0.06 to 2.16 ± 0.01 and onion ranged from -1.0 ± 0.06 to 5.0 ± 0.06; highest is Cd (5 µg / L) found in onion, lowest is Pb (- 1.2 µg / L) in cucumber respectively. Values obtained falls within the recommended standard values by WHO / FAO. Conclusively, these vegetables cultivated in Damboa area was found to be wholesome and fit for consumption as at the time of this analysis.